Model organism proteomics as a tool for the study of host–microbiome interactions. Issue 10 (25th June 2014) - Cassidy, Liam; Tholey, Andreas
Abstract : All organisms live in constant contact with the microbial world. In recent years it has become evident that these microbial communities are not only responsible for the development of certain diseases, but are also an indispensable factor for homeostasis. The inherent complexity of meta‐organisms hampers a straightforward elucidation of the molecular processes regulating the interactions of the host and its microbiome, as well as the influence of exogenic factors, for example, nutrition. Modern approaches such as meta‐proteomics are now capable of deciphering the major processes in microbial communities, but the complete analysis of their interactions with their host is still in its infancy. In order to get easier access, the study of nonmammalian model organisms bears great potential. These organisms provide advantages such as reduced complexity, ease of cultivation in great numbers, and amenity to a range of genetic and biochemical manipulations. We highlight the potentials provided by model organism proteomics for the study of host–microbiome interactions and outline major challenges and demands for technological improvements that will be necessary for the understanding of the manifold interactions within meta‐organisms.